Efficacy of three different pulpotomy agents in primary molars: a randomized control trial. (6th March 2016) - Rajasekharan, S.; Martens, L. C.; Vandenbulcke, J.; Jacquet, W.; Bottenberg, P.; Cauwels, R. G. E. C.
Abstract: Aim: To compare the clinical and radiographic efficacy of Biodentine ™, ProRoot ® White Mineral Trioxide Aggregate (WMTA) and Tempophore ™ as pulpotomy medicaments in the treatment of carious primary molars. Methodology: A parallel‐design, randomized controlled trial was developed. Patients above 3 years of age with carious primary teeth with vital pulps without spontaneous pain or history of swelling were included. Fifty‐eight patients (82 teeth) with a mean age of 4.79 ± 1.23 years were included. The teeth were randomized, blinded and allocated to one of the three groups (Biodentine ™, ProRoot ® WMTA or Tempophore ™ ) for pulpotomy treatment. All teeth were followed up clinically and radiographically (after 6, 12 and 18 months) by two blinded calibrated investigators. A generalized estimating equation (GEE), Wald chi‐square test and an intention‐to‐treat analysis (ITT) with 'last carried forward' approach were performed using Statistical Package for Social Sciences v 21.0 (IBM Corp., Armonk, NK, USA). Results: Forty‐six patients and 69 teeth were available for follow‐up after 18 months. Clinical success (radiographic success in parenthesis) was 95.24% (94.4%), 100% (90.9%) and 95.65% (82.4%) in the Biodentine ™, ProRoot ® WMTA and Tempophore ™ groups, respectively, but the difference was not significant. Pulp canal obliteration was significantly different amongst the experimental groups as the Biodentine ™ group exhibited significantly more pulp canal obliteration when compared to the ProRoot ® WMTA group at 6 months ( P = 0.008) and 18 months ( P = 0.003). Conclusions: After 18‐month follow‐up, there was no significant difference between Biodentine ™ in comparison with ProRoot ® WMTA or Tempophore ™ .